O racismo estrutural como limite: às políticas públicas de combate à discriminação - Pereira, Eduardo Santiago (2018)
This thesis analyzes the limits that structural racism imposes on the development of public policies concerned to the fight against racial discrimination. Its research problem is based on the necessity to verify how the articulation between structural racism and the ideology of whiteness makes it difficult to enforce racial equality policies in the area of public security. Therefore, it was established as a general objective to analyze the role and effects of these phenomena in such policies. As specific objectives were determined to understand how racism, in its most diverse manifestations, would influence the conception of that kind of public policies; to identify the importance of structural racism and the ideology of whiteness in the contemporary Brazilian society; to verify the effects of racism on legal order and to the police forces practice; to describe how the intersectionality of categories such as race, color, gender, class, income and origin would help to maintain racism and discrimination; and to determine rules that could help in the elaboration of public security policies that take into account such intersectionality. Based on the fact that the racialized organization of contemporary society brings us a pattern of values, customs and attitudes that are determined by an ideology aimed at maintaining whiteness as a pattern of sociability, this research is dedicated to identifying how the advantages and the privileges of the white race naturalize and justify economic inequalities, removing the perception that such conflicts would be due to the racial phenomenon and that it would be reflected in the modus operandi of the public security agents. With regard to the conclusions and results achieved, should be highlighted the importance of reducing personal decisions of public security agents in the execution of their legal duties, through the development of specific protocols to regulate their actions when carrying out activities that may result in violation of the rights of black citizens. Hence, it has been realized that structural racism and the ideology of whiteness in public security need to be done through public policies capable of identifying them and making them explicit, so that it will be possible to recognize their influence on the actions of police officers.